Studying and forecasting the evolution of the Day river coastal zone up to the year of 2070 - Hung, Duong Quoc; Dang, Vu Hai; Pha, Phan Dong; Nguyet, Nguyen Thi Anh; Huong, Ngo Bich; Son, Nguyen Thai (Vietnam Journal of Marine Science and Technology, 2020)
The Day river coastal zone is the place of plentiful and eventful economical activities and the natural habitat of diverse endemic species that should be preserved and developed. According to the updated geological, remote-sensing and oceanographic data sources, this study figures out the actual state, evolutional history and forecasts the development of the Day river coastal zone up to the year 2070, which could be used to improve the effectiveness of the long-term spatial coastal zone management and master planning. Major conclusions are as follows: (i) The Day river coastline has been highly modified since the last 50 years, (ii) The shoreline seaward development tends to gradually decrease in recent years, and (iii) The river-bed continues to be shifted southwestwards in the context of global climate change and sea level rise.